PRRT2 mutations: exploring the phenotypical boundaries. Issue 4 (7th October 2013) - Djémié, Tania; Weckhuysen, Sarah; Holmgren, Philip; Hardies, Katia; Van Dyck, Tine; Hendrickx, Rik; Schoonjans, An-Sofie; Van Paesschen, Wim; Jansen, Anna C; De Meirleir, Linda; Selim, Laila Abdel Moteleb; Girgis, Marian Y; et al.
Abstract : Background: Mutations in the proline-rich transmembrane protein 2 ( PRRT2 ) gene have been identified in patients with benign (familial) infantile convulsions (B(F)IC), infantile convulsions with choreoathetosis (ICCA) and paroxysmal dyskinesias (PDs). However it remains unknown whether PRRT2 mutations are causal in other epilepsy syndromes. After we discovered a PRRT2 mutation in a large family with ICCA containing one individual with febrile seizures (FS) and one individual with West syndrome, we analysed PRRT2 in a heterogeneous cohort of patients with different types of infantile epilepsy. Methods: We screened a cohort of 460 patients with B(F)IC or ICCA, fever related seizures or infantile epileptic encephalopathies. All patients were tested for point mutations using direct sequencing. Results: We identified heterozygous mutations in 16 individuals: 10 familial and 6 sporadic cases. All patients were diagnosed with B(F)IC, ICCA or PD. We were not able to detect mutations in any of the other epilepsy syndromes. Several mutation carriers had learning disabilities and/or impaired fine motor skills later in life. Conclusions: PRRT2 mutations do not seem to be involved in the aetiology of FS or infantile epileptic encephalopathies. Therefore B(F)IC, ICCA and PD remain the core phenotypes associated with PRRT2 mutations. The presence of learning disabilities or neuropsychiatric problems in several mutation carriers calls for additional clinical studies addressing this developmental aspect in more detail.